Työkyvyttömyyden lääketieteellisen arvioinnin vaikeudet ja eläkkeiden hylkääminen : Kelan selvitys eläkehakemusten B-lomakekäytännöistä - Virta, Lauri, 1955- (Turku : Kansaneläkelaitos, tutkimus- ja kehitysyksikkö, 2001)
Summary.
Summary: Medical assessment of disability and rejection of pension applications.
Summary : Medical assessment of disability and rejection of pension applications : a survey on the use of different types of form B in disability pension applications.
Summary: Medical assessment of disability and rejection of pension applications: A survey on a use of different types of form B in disability pension applications.
Keywords: Pensions; Expert Testimony; Disability Evaluation; Work Capacity Evaluation; lääketiede; eläkkeet; ongelmat; työkyvyttömyys; työkyky; arviointi; työkyvyttömyyseläkkeet; hakemukset; lääkärinlausunnot; lomakkeet; vakuutuslääketiede; hylkäyspäätökset; sosiaaliturva; kuntoutus; medicin; pensioner; problem; arbetsoförmåga; arbetsförmåga; utvärdering; invalidpensioner; ansökningar; läkarutlåtanden; blanketter; försäkringsmedicin; socialskydd; rehabilitering (vård); avslagsbeslut